Total Quality Management di SDN 100 Bengkulu Utara - A. Tsabat Izzudin; Sri Susilowardani (Journal on Education, 2023)
TQM at SDN 100 is interesting to study because every SDN or educational institution has tips for improving the quality of all aspects of the institution. It also explains what TQM is and what its implementation is. Lack of understanding of TQM and ultimately the output is not on target. This research uses observation or qualitative research which is based on interviews on every aspect of the SDN 100 environment. The quality of SDN 100 is more than adequate than public SDN in general, the facilities that students get are many, such as good facilities, large prayer rooms, libraries with educational materials. complete readings and teaching staff according to dapodik and majors taken in sync with the subjects being taught. For the biggest income from BOS funds and plantations around the school area.